Understanding the impact of artificial intelligence on the stock market development in BRICS nations: a panel ARDL method - V RESHMA; Pradeesh K.; Mohandas V K; K. MANIKANDAN (Theoretical and Applied Economics)

(untitled)
The stock market is considered an essential marketplace that unites savers and borrowers, generating liquidity that enables governments, businesses, and individuals to trade shares, which is crucial for economic growth. With the integration of artificial intelligence in the financial market, there have been considerable changes in trade strategies, risk management, and market forecasting. Thus, the present study examines the impact of artificial intelligence (AI) on the stock market (SM) along with other factors such as trade (tr), foreign investment (FDI), exchange rate (Ex), and inflation (In) from 2000 to 2022 in BRICS nations. BRICS countries were particularly selected due to the high potential for investment. According to the results of the first- and second-generation panel unit root tests, there are no unit root issues, and the factors have a mixed order of integration. The long-term cointegration of the factors is validated by the panel cointegration test. The results show that artificial intelligence, FDI, and trade have a positive effect on the stock market, whereas exchange rate and inflation have a negative effect. While in the short run, all factors except trade have a positive impact on SM in BRICS nations. These panel ARDL results were further validated by employing Augmented Mean Group (AMG) and Common Correlated Effects Mean Group (CCEMG). Furthermore, employing the Dumitrescu-Hurlin causality test, a bidirectional causal relationship was found between the stock market and FDI and the stock market and trade. A unidirectional causality was found between AI and the stock market. The findings suggested that policymakers should concentrate more on investment policies and integrating AI techniques for the development of the stock market.